2022
DOI: 10.3390/w14203313
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Methylene Blue Dye Using Biodegradable Superabsorbent Hydrogel Polymer Composite Incorporated with Activated Charcoal

Abstract: Hydrogels have attracted great attention as good adsorbents due to their extraordinary water retention capacity, unique hydrophilic nature, biocompatibility, and abundance in availability. In this work, a superabsorbent polymer (SAP) hydrogel and its composite were synthesized, with the introduction of activated charcoal (SAP-AC) for deep removal of the ecotoxic organic dye methylene blue (MB). The formation of the hydrogel was confirmed by FTIR analysis, and scanning electron microscopy (SEM) revealed the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…[ 41 ] Anionic MCS achieved significant MB adsorption within a 2 h immersion, reaching an equilibrium adsorption capacity of 110.36 ± 9.63 mg g −1 , attributed to the formation of ionic complexes between MB and the COO − groups in the superadsorbent network. [ 42 , 43 ] Overall, the robust adsorption of photosensitizer molecules is anticipated to be critical for the light‐activated self‐sanitizing function of MCS.…”
Section: Resultsmentioning
confidence: 99%
“…[ 41 ] Anionic MCS achieved significant MB adsorption within a 2 h immersion, reaching an equilibrium adsorption capacity of 110.36 ± 9.63 mg g −1 , attributed to the formation of ionic complexes between MB and the COO − groups in the superadsorbent network. [ 42 , 43 ] Overall, the robust adsorption of photosensitizer molecules is anticipated to be critical for the light‐activated self‐sanitizing function of MCS.…”
Section: Resultsmentioning
confidence: 99%
“…SHs are recently getting concerned with sanitary and hygiene applications studied by Peenal et al [13]. Syed Sikandar Shah et al reported that the SHs can also be incorporated with activated charcoal for selective adsorption of methylene blue dye which shows an excellent result [14]. In our previous work, we prepared APTAC-AAc hydrogel whose maximum equilibrium swelling was found to be 246 g/g of gel [15].…”
Section: Introductionmentioning
confidence: 89%
“…Due to the extensive area of application, hydrogels are getting concern worldwide. A few of the SHs are very effective in selective metal adsorption [5], drug delivery [6], dye adsorption [7], wound dressing [8], and biomedical applications [9]. The essential properties of hydrogels are swelling, mechanical strength, and re-usability, which can be enriched through grafting/cross-linking between different monomers/polymers [10,11].…”
Section: Introductionmentioning
confidence: 99%